Assessing the Challenges of Shea Butter Processing on Sustainable Livelihood of Women in the Sagnaregu Municipality of the Northern Region of Ghana - Mumin, Alhassan Abdul; Mordzeh-Ekpampo, Musah Ibrahim; Boasu, Bismark Yeboah; Yahaya, Tia; Abdulai, Shawaratu (Journal of Social Science Studies, 2023)
This study assessed women and sustainable livelihoods with focus on selected shea butter processing centers in Sagnarigu Municipal Assembly of the Northern Region, Ghana. The objectives of the study were to determine the challenges confronting women into shea butter processing and to examine the extent to which these challenges undermine sustainable livelihood of women. This study adopted the explanatory research designs with the quantitative research strategy. The study used structured questionnaire to gather data from 240 women. The study used Structural Equation Model to identify the challenges that significantly undermine sustainable livelihood of women. Start-up capital and credit for equipment, raw material and labor were financial challenges. Leadership, conflicts on transparency and accountability and social status were social challenges. Inadequate technical skills, poor management skills, poor record keeping were human capital challenges. Poor road network, inadequate storage facilities were physical challenges. Poor community and governmental relationship was the major institutional challenge. This study recommends urgent need to address institutional, natural capital and financial challenges confronting women into shea butter processing in the study area.